2022
DOI: 10.3390/ijms23063237
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Transcriptome and RNA-Seq Analyses Reveal the Mechanisms Underlying Waterlogging Tolerance in Kiwifruit (Actinidia valvata)

Abstract: Actinidia valvata possesses waterlogging tolerance; however, the mechanisms underlying this trait are poorly characterized. Here, we performed a transcriptome analysis by combining single-molecule real-time (SMRT) sequencing and Illumina RNA sequencing and investigated the physiological responses of the roots of KR5 (A. valvata, a tolerant genotype) after 0, 12, 24 and 72 h of waterlogging stress. KR5 roots responded to waterlogging stress mainly via carbohydrate and free amino acids metabolism and reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 97 publications
2
8
0
Order By: Relevance
“…Results showed that the obtained sequencing data in the present study was reliable and our waterlogged treatment of kiwifruit roots was effective (Figure 2). Previous studies have provided information on variations in the number of responded transcripts of kiwifruit genotypes with different tolerance levels under oxygen deprivation stress [28][29][30]. In this study, we found that there were more up-regulated DEGs than down-regulated ones (Figure 3), indicating the expression induction and enhancement of gene function were more responsible in response to waterlogging stress of A. deliciosa roots, consistent with previous study in A. valvata [30].…”
Section: Discussionsupporting
confidence: 90%
“…Results showed that the obtained sequencing data in the present study was reliable and our waterlogged treatment of kiwifruit roots was effective (Figure 2). Previous studies have provided information on variations in the number of responded transcripts of kiwifruit genotypes with different tolerance levels under oxygen deprivation stress [28][29][30]. In this study, we found that there were more up-regulated DEGs than down-regulated ones (Figure 3), indicating the expression induction and enhancement of gene function were more responsible in response to waterlogging stress of A. deliciosa roots, consistent with previous study in A. valvata [30].…”
Section: Discussionsupporting
confidence: 90%
“…Within the Italian kiwifruit sector, this practice has not been widely used before. We have, therefore, screened genotypes of different Actinidia species intended for use as rootstocks or for breeding programs for their putative resistance or tolerance to KVDS [27,29,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation sequencing technology holds great potential for improved transcript detection compared to second-generation sequencing techniques such as RNA-seq. This has been demonstrated through its successful applications in a variety of plants [31][32][33][34]. The current study provided comprehensive landscapes of isoform full-length sequences, gene structures, lncRNAs, and AS events.…”
Section: High-quality Data Obtained From Pacbio Transcriptome Sequencingmentioning
confidence: 87%